ANALISIS SISTEM PENGELOLAAN OBAT DI INSTALASI FARMASI RAWAT JALAN RUMAH SAKIT DAERAH MADANI KOTA PEKANBARU - Yuliana, Anastasya Shinta; Melan, Meilani Eka Wijaya; Salim, Agus; Zaky, Abdul (Journal of Hospital Administration and Management (JHAM), 2023)
The medicine management system is part of the provision of health services in hospitals. The lack of smooth medicine management will have a negative impact on hospitals, both medically, socially and economically. Medicine management at the Madani Regional Hospital in Pekanbaru City, the level of medicine availability has not been in accordance with needs. This study aims to determine the medicine management system in outpatient pharmaceutical installations of Madani Regional Hospital in Pekanbaru City. This type of research is qualitative with a descriptive analytical approach. The study was conducted on March 27 - August 10, 2023 at the Madani Regional Hospital in Pekanbaru City. There were 6 research informants and the research used the Content Analysis model.The results of the study are types of medicine based on proposals, income, and utilization, planning constraints regarding changes in disease patterns, demand, medicine vacancies, medicine planning from disease epidemiology, lack of e- catalog such as airing and others, e-catalog takes precedence according to the rules, there is no special training, medicine availability is not appropriate, warehouse space is less spacious, temperature and layout are not appropriate, lack of trolleys, which affects storage, namely space, temperature and safety, medicine distribution constraints such as systems, stock constraints, communication and accuracy.Is recommended that there is medicine planning from the number of medicine use, patient visits and disease epidemiology, systematic planning according to Standard Operating Procedures so that medicine needs are fulfilled, training is held, especially the use of e-catalog so that officers understand, expanded warehouse space and added air conditioning so that not many medicine are damaged, there is a secure code on the pharmacy door to maintain room security, there are officers on duty to distribute medicine so that there are no delays, There is a medicine distribution flow on display, medicine are stored in cabinets, shelves and special rooms.